Komunikasi Kooperatif D2D dengan Bantuan UAV Berbasis AF/DF Multi Relay dengan Dampak Hardware Impairment - Annysa Aprilya; Meyra Chusna Mayarakaca; Arifin; Faridatun Nadziroh; Yoedy Moegiharto (Politeknik Negeri Malang, 2024)
This work investigates the implementation of hybrid AF and DF relay protocols in D2D multi-relay wireless communication systems. To obtain system performance we propose four scenarios for using the AF and DF relay protocols and three S – R and R – D distance conditions that have an impact on system performance in terms of throughput values. From the simulation results it is concluded that the R – D distance will produce the highest SNR value which produces the best system throughput value compared to . The simulation results also prove that applying the AF relay protocol to all relays produces better SNR values ​​and better throughput values ​​than applying the DF relay protocol. Simulation results with the impact of hardware impairment (HI) levels show that system performance in the first scenario is actually worse than other scenarios when the κ value is above 0.1.